A Biosensing Strategy for Fast Profiling of Antibiotic Resistance. (2017) - Mecklenburg, Michael; Chen, Qun; Andersson, Anneli; Xie, Bin
Abstract: Antibiotic resistance threatens global public health. Clinical methods that simplify and accelerate resistance diagnosis are urgently needed. Here we describe a function-based antibiotic resistance detection and classification strategy to improve diagnosis. The method identifies resistance enzymes by directly measuring the thermal signal generated when an antibiotic i enzymatically degraded. A substrate specificity profile is created by analyzing a panel of antibiotics. Here we show proof of principle by differentiating two antibiotic resistance enzymes based on their substrate specificities profiles. The method provides a fast, simple, cost effective alternative for diagnosing and classifying antibiotic resistance.